HUBUNGAN ANTARA TINGKAT PENGETAHUAN KADER MASYARAKAT PEDULI PARU SEHAT DENGANoKEPATUHANoBEROBAToPASIEN TUBERKULOSIS DIjBALAI KESEHATANjMASYARAKAT WILAYAH SEMARANG - Rissa Amalia Rachmah; Lintang Dian Saraswati; Praba Ginandjar (Jurnal Kesehatan Masyarakat (Undip), 2019)
Tuberculosis (TB) is an infectiousjdisease which is still the highest cause of death in Semarang. The purposejofjthis study was to describe and analyze the factors that Madupahat community related to tuberculosis patients adherence in Balkesmas Semarang Regional. This study used a crossjsectional study design. The studyjpopulation was all Madupahat community who became PMOs of TB patients who were treated at the Balkesmas Semarang Regional, as many as 43 respondents. There are middle-aged adults (72.1%), female sex (62.8%), working as housewives (39.5%), and having a secondary education level (67, 4%). The bivariate analysis utilized Chi Square test with 95% significance. The result of bivariate analysis demonstrates level of knowledge (p=0,010). Madupahat community is expected to be able to maximize the training program so that knowledge about TB can increase.